2017
DOI: 10.1155/2017/8936060
|View full text |Cite
|
Sign up to set email alerts
|

Performance ofClarias gariepinusFed Dried Brewer’s Yeast(Saccharomyces cerevisiae)Slurry in Replacement for Soybean Meal

Abstract: Following disparity of earlier results, this study tested the performance of African catfish Clarias gariepinus fed dried brewer's yeast slurry meal (DBYM) based diets. Fingerlings of C. gariepinus with pooled mean initial weight of 1.58 ± 0.01 g were stocked in hapas (1 m × 1 m × 1 m) immersed in an earthen pond at a density of 15 fish per cage. Five diets with increasing substitution of soybean meal with 25%, 50%, 75%, and 100% of dried brewer's yeast and a control without dried brewer's yeast (0% substituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
9
1
1
Order By: Relevance
“…Rumsey, Winfree, and Hughes (1992) implicated purine bases as being responsible for the depressing feed intake in farm animals. Also in contrast to the findings of the current study, Solomon, Ataguba, and Itodo (2017) observed a reduction in feed intake in African catfish, Clarias gariepinus, fed a brewer's yeast diet compared to those fed a soybean diet.…”
Section: Growth Performance and Fcecontrasting
confidence: 99%
“…Rumsey, Winfree, and Hughes (1992) implicated purine bases as being responsible for the depressing feed intake in farm animals. Also in contrast to the findings of the current study, Solomon, Ataguba, and Itodo (2017) observed a reduction in feed intake in African catfish, Clarias gariepinus, fed a brewer's yeast diet compared to those fed a soybean diet.…”
Section: Growth Performance and Fcecontrasting
confidence: 99%
“…Rumsey et al (1991) reported that diet containing 25% brewer's dried yeast when fed to rainbow trout grew better.Oliva- Teles and Goncalves (2001) found that up to 30% brewers yeast in the diet improved feed efficiencyand 50% of the fish meal in a totally fish meal protein-based diet can be replaced with brewer's yeast in sea bass, Dicentrarchus labrax, with no adverse effect on growth. Solomon et al (2017) concluded that the optimal range of inclusion and substitution of soybean meal with dried brewer's yeast slurry meal in C. gariepinus feed liesup to 14% of dry matter.…”
Section: Breweries Waste (Bw)mentioning
confidence: 99%
“…Sinh khối nấm men được sử dụng rộng rãi như nguồn cung cấp protein cho người và động vật trong thức ăn chăn nuôi hoặc các sản phẩm bổ sung cho con người (Halász, Lásztity, 1990;Solomon et al, 2017). Nhiều nghiên cứu đã sử dụng chủng nấm men S.cerevisiae để sản xuất protein đơn bào, glucan, carotenoid (Bekatorou et al, 2006;Kwiatkowski, Kwiatkowski, 2012;Mata-Gómez et al, 2014).…”
Section: Mở đầUunclassified